2015
DOI: 10.1007/s11747-015-0443-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the tension between consistency and relevance: design thinking as a mechanism for brand ambidexterity

Abstract: In order to sustain and grow brand equity, brand managers are faced with balancing the preservation of existing brand identity through consistency with the need to maintain relevance, which requires change and innovation. In this paper we build upon the concept of organizational ambidexterity (March 1991), arguing that design thinking-the logics and practices associated with designers-can serve as a mechanism which promotes and enables the integration of brand consistency and relevance. Drawing on cases of inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 159 publications
(189 citation statements)
references
References 90 publications
3
183
0
3
Order By: Relevance
“…Design thinking has been described as an iterative approach “characterized by trial‐and‐error learning […] that tests a range of possible solutions with end‐users and other project stakeholders” (Beverland et al, , p. 593). Iteration is utilized to clarify the problem being addressed (Beckman and Barry, ) and to trigger cycles of problem definition and experimental solution creation (Rylander, ), often involving deep user research to develop insights (Liedtka, ).…”
Section: Principal Attributes Of Design Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Design thinking has been described as an iterative approach “characterized by trial‐and‐error learning […] that tests a range of possible solutions with end‐users and other project stakeholders” (Beverland et al, , p. 593). Iteration is utilized to clarify the problem being addressed (Beckman and Barry, ) and to trigger cycles of problem definition and experimental solution creation (Rylander, ), often involving deep user research to develop insights (Liedtka, ).…”
Section: Principal Attributes Of Design Thinkingmentioning
confidence: 99%
“…Remarkably, despite compelling calls for the adoption of design thinking (e.g., Luchs, ), a generally accepted definition is still lacking, “and even the term itself is a subject of controversy among its practitioners and advocates” (Liedtka, , p. 926). In fact, there appear to be substantial differences between promoters and critics of design thinking about what it is and what it can do (see, e.g., Beverland, Wilner, and Micheli, ; Brown, ; Johansson‐Sköldberg, Woodilla, and Çetinkaya, ; Kimbell, ; Liedtka, ; Martin, ). For example, some authors have considered it to be an organizational attribute, whereas others conceive of it at the individual level, highlighting the traits of “design thinkers” (see, e.g., Brown and Katz, ; Luchs, ).…”
Section: Introductionmentioning
confidence: 99%
“…Beverland, Wilner, & Micheli (2015) identified that design as process involved abductive thinking (asking 'what might be?' questions), iteration and experimentation (ongoing trial and error, prototyping, adaptation and co-creation with users), holism (looking at problems in context) and user-centredness (a focus on experience, emotion and meaning, and distinct from customer orientation as it focuses on latent needs as defined by the user's engagement with sociocultural contexts) as common themes amongst writers on design practices.…”
Section: Design Processmentioning
confidence: 99%
“…In regard to marketing, design as process research has already offered insights into new methods of product innovation (Verganti, 2009; see also Tabeau et al, 2017), leveraging cultural insights for brand meaning (Wilner & Huff, 2017), addressing wicked branding problems (Beverland et al, 2015;Wilner & Ghassan, 2017) and enhancing interfunctional coordination with NPD (Beverland et al, 2016). Research should of course build on these domains but also address other enduring challenges facing the marketing organisation.…”
Section: Design Processmentioning
confidence: 99%
“…Other scholars have focused on the impact of reducing the psychological distance between functions through the creation of a shared syntax or language (Carlile, 2002), for example through the development of a unified culture around market orientation or design thinking (Beverland, Wilner and Micheli, 2015). However, such attempts have been found to come at the cost of effectiveness (Fisher, Maltz and Jaworski, 1997;Krohmer, Homburg and Workman, 2002).…”
Section: Npd Success and Interfunctional Coordinationmentioning
confidence: 99%